Benign ethnic neutropenia: What is a normal absolute neutrophil count? - Haddy, Theresa B.; Rana, Sohail R.; Castro, Oswaldo (The Journal of laboratory and clinical medicine, 1999)
Approximately 25% to 50% of persons of African descent and some ethnic groups in the Middle East have benign ethnic neutropenia, with low leukocyte and neutrophil counts. It is important to recognize the existence of this condition, the most common form of neutropenia throughout the world, and thus avoid both under- and overevaluation. Although there is no scientific basis for an absolute neutrophil count of 1.5 × 109/L to be considered minimal, counts below this level are empirically regarded as inadequate in persons of all ethnic groups who are above the age of 1 year.1-4 Many individuals, however, maintain consistently low absolute neutrophil counts without evidence of increased susceptibility to infection or any other adverse effect. The important determination is not how many neutrophils are present in the peripheral blood, but whether the bone marrow is able to produce enough normally functioning cells when needed.5-9 A description of benign ethnic neutropenia, as set forth in this review, suggests that the lower limit now considered acceptable for the absolute neutrophil count should be readjusted downward for all ethnic groups. (J Lab Clin Med 1999;133:15-22)